Autologous Patellar Tendon Reconstruction after Total Knee Arthroplasty Infection with Skin Loss: Anatomical Study and Case Report - Pérez-García, Alberto; Esteban-Vico, Juan Ramon; García-Sánchez, Jose María; Baeza, José; Soriano, Francisco Martínez; Valverde Navarro, Alfonso Amador; García-Granero, Álvaro; Simón-Sanz, Eduardo (The Journal of Knee Surgery, 2020)
Disruption of patellar tendon after total knee arthroplasty (TKA) is a devastating complication. If associated with infection or soft tissue defect, knee arthrodesis is usually indicated. The purpose of this study is to analyze, by means of an anatomical study, the feasibility of our novel technique for reconstruction of extensor apparatus after TKA infections with skin defects, combining gracilis (G) and semitendinosus (ST) tendon autografts and chimeric medial gastrocnemius-sural artery perforator (SAP) flap. In addition, to report on the use of this reconstruction, we described an illustrative clinical case. Ten fresh cadaver lower limbs were dissected. The width of the gastrocnemius, number of medial SAP, length of hamstrings tendons, and distance from the lower pole of the patella to anterior tibial tuberosity (ATT) were measured. A mean of 1.37 perforator branches (range 1–3) was found. In all cases, the tendon length for gracilis and ST, and the width in the middle third of gastrocnemius related to the patella-ATT distance were enough to make the reconstruction. We performed this technique in a 78-year-old man with an infected TKA with skin defect. After 1 year and two-stage procedure, the patient achieved full active knee extension and was able to ambulate without aids. Extensor apparatus reconstruction combining tendon autografts and chimeric medial gastrocnemius-SAP flap is an available technique and may be considered as an alternative to arthrodesis in extensor mechanism ruptures after infection in TKA.
Keywords: total knee arthroplasty; extensor mechanism; infection; autograft reconstruction; chimeric medial gastrocnemius-SAP flap